1999
DOI: 10.1104/pp.119.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Flux Is Adjusted to Nitrogenase Activity in Nodules of Detopped and Argon-Treated Alfalfa Plants1

Abstract: To investigate the short-term (30-240 min) interactions among nitrogenase activity, NH 4 ؉ assimilation, and plant glycolysis, we measured the concentrations of selected C and N metabolites in alfalfa (Medicago sativa L.) root nodules after detopping and during continuous exposure of the nodulated roots to Ar:O 2 (80:20, v/v). Both treatments caused an increase in the ratios of glucose-6-phosphate to fructose-1,6-bisphosphate, fructose-6-phosphate to fructose-1,6-bisphosphate, phosphoenolpyruvate (PEP) to py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…We found an increase in the concentration of free amino acids in the vascular tissue of the plant and suggest that it triggers a reduced oxygen permeability in the nodules, which leads to the down-regulation of nitrogenase activity [6,11,27]. This may lead to N limitation of the GS/GOGAT cycle and, thus, to an increase in the Glu/Gln ratio and to an appropriate adaptation of the glycolytic pathway [4]. The decrease in the concentration of sucrose in the phloem is considered not to be associated with the decreased nitrogenase activity [4,12,27,28].…”
Section: Amino Acidmentioning
confidence: 92%
See 2 more Smart Citations
“…We found an increase in the concentration of free amino acids in the vascular tissue of the plant and suggest that it triggers a reduced oxygen permeability in the nodules, which leads to the down-regulation of nitrogenase activity [6,11,27]. This may lead to N limitation of the GS/GOGAT cycle and, thus, to an increase in the Glu/Gln ratio and to an appropriate adaptation of the glycolytic pathway [4]. The decrease in the concentration of sucrose in the phloem is considered not to be associated with the decreased nitrogenase activity [4,12,27,28].…”
Section: Amino Acidmentioning
confidence: 92%
“…This may lead to N limitation of the GS/GOGAT cycle and, thus, to an increase in the Glu/Gln ratio and to an appropriate adaptation of the glycolytic pathway [4]. The decrease in the concentration of sucrose in the phloem is considered not to be associated with the decreased nitrogenase activity [4,12,27,28].…”
Section: Amino Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenylates and Regulation of Glycolytic Flux in Ar-Exposed Nodules Curioni et al (1999) found direct evidence linking N deprivation to glycolytic flux in alfalfa (Medicago sativa) nodules exposed to Ar:O 2 . The Glu-Gln ratio increased 5-fold during the first 30 min, while malate concentration declined and Suc accumulated.…”
Section: Effect Of Ar:o 2 On Adenylate Pools In Subcellular Compartmementioning
confidence: 95%
“…The study also showed ratios of Fru-6-phosphate to Fru-1,6-bisphosphate and phosphoenolpyruvate to pyruvate to increase after 30 min Ar-exposure, consistent with a negative effect of N deprivation on the activity of phosphofructokinase (PFK) and pyruvate kinase. Although it was proposed that the increased Glu-Gln ratio, caused by NH 4 1 unavailability, may act as a signal to decrease plant glycolytic flux (Curioni et al, 1999), a role for adenylates, and specifically elevated ATP, can be envisaged. Since the turnover of ATP and ADP is coupled to several steps in both NH 4 1 assimilation and glycolysis, we propose that the observed increase in cytosolic ATP-ADP ratio in Ar (this study) will inhibit the activity of some key glycolytic enzymes, resulting in a reduced C-flux through the pathway.…”
Section: Effect Of Ar:o 2 On Adenylate Pools In Subcellular Compartmementioning
confidence: 99%